(untitled) (Al-Academy, 2025)
The objective study of the systematic progression in architectural designs in terms of their design configurations and their importance within the interior space of the entrances to Islamic palaces and how to implement them is considered an important matter in the interior design of all Islamic palaces, as they represent a distinctive feature as a fine art...and the interior designer can touch aspects of this development. In the types of architectural designs as a result of the urban development of palaces, and here the research problem question arises, concerned with understanding the main role, which is formulated as follows: How is the systematic progression achieved in Al-Riyaza architecture? How does this stylistic progression have an impact on Islamic internal spaces?While the second chapter included the theoretical framework and the indicators that came out of it that addressed the topic of stylistic gradation and its relationship to the architectural leadership of Islamic interior spaces, the research procedures were within the third chapter, where two models of interior designs for Islamic palaces were analysed, and the most important results were the diversity in the vocabulary of raw materials and materials adopted in the design of entrances. Its effects became clear in the visual appearance within design techniques intertwined between the prominent and the recessed, which contributed to the emergence of design formations whose features were revealed within the interplay between smooth and rough materials, which achieved aesthetic value for the palace entrances, including (brick, stone, tile, marble, wood, And the decorative squares) were achieved in the first model and achieved in the second model, as confirmed by the designer’s study of the decorative units that are classified into dynamic ones, including (monotonous, non-monotonic, and free), as they were achieved in the first model and relatively achieved in the second model. The aesthetic need to show The design role of architectural leadership for the entrances of Islamic palaces through the diversity of decorations for the designs of the interior spaces of the palace entrances, including geometric decoration, floral decoration, written decoration, architectural decoration, and abstract decoration, which in light of this contributed to achieving their aesthetic values. They were achieved in the first model and were achieved in the second model.